2005
DOI: 10.1111/j.1471-4159.2004.02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia sensitizes human malignant glioma cells towards CD95L‐induced cell death

Abstract: Death ligands such as CD95 ligand (CD95L) have limited activity against glioma cells under normoxic conditions. Hypoxia is a critical aspect of the microenvironment of gliomas in vivo. We investigated the effect of co-exposure to acute hypoxia and CD95 ligand in three human malignant glioma cell lines with different susceptibility to CD95L under normoxic conditions. Hypoxia sensitized all three cell lines towards CD95L-induced cell death. Co-exposure resulted in apoptotic changes in the early phase, with gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Profound hypoxia (0.1% O 2 ) was induced by incubating cells in Gas Pak pouches for anaerobic culture (Becton-Dickinson, Heidelberg, Germany) (Steinbach et al, 2003). Moderate hypoxia (1% O 2 ) was induced in a Labotect incubator (Goettingen, Germany).…”
Section: Induction Of Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…Profound hypoxia (0.1% O 2 ) was induced by incubating cells in Gas Pak pouches for anaerobic culture (Becton-Dickinson, Heidelberg, Germany) (Steinbach et al, 2003). Moderate hypoxia (1% O 2 ) was induced in a Labotect incubator (Goettingen, Germany).…”
Section: Induction Of Hypoxiamentioning
confidence: 99%
“…Thereafter, cells were washed with cold phosphate-buffered saline and lysed in lysis buffer (50 mM Tris-HCl (pH 8), 120 mM NaCl, 5 mM EDTA, 0.5% NP-40) containing protease inhibitors (Roche, Mannheim, Germany). Cellular lysates were prepared as described (Steinbach et al, 2003) and subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Membranes were probed with antibodies to human p53 (sc-263; Santa Cruz, San Diego, CA, USA), murine p53 (p53-Ab-4; Merck, Darmstadt, Germany), GAPDH (MAB374; Chemicon, Nuernberg, Germany), AMPKa (2531; Cell Signaling, Frankfurt am Main, Germany), phospho-AMPKa (2531; Cell Signaling), acetyl coA carboxylase (3662; Cell Signaling), phospho-acetyl coA carboxylase (3661; Cell Signaling), actin (SC1616; Santa Cruz) or phospho-4E binding protein 1 (9459; Cell Signaling).…”
Section: Induction Of Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Cells synchronically grown in cell culture flasks were prepared for electron microscopy as described earlier (13). Specimens were analysed and documented with an EM 10A electron microscope (Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…However, under the conditions of the tumor microenvironment, inhibition of the EGFR-PI3K/Akt-mTOR cascade may also have negative consequences, because it may affect the sensitivity towards starvation. We have recently reported that, in malignant glioma cells, inhibition of EGFR, Akt and mTOR profoundly reduces energy consumption and thereby provides protection against hypoxic stress [26][27][28]. Given the increasingly evident role of hypoxia as a key selective pressure for solid tumors and the prominent occurrence of hypoxia in gliomas, spontaneously or potentially induced by antiangiogenic therapies [29,30], this mechanism may limit the efficacy of anti-EGFR and anti-mTOR therapies.…”
Section: Egfr and Mtor: Key Factors In The Biology Of Malignant Gliomasmentioning
confidence: 98%